A Solid Supported Membrane-Based Technology for Electrophysical Screening of B0AT1-Modulating Compounds. (July 2021) - Gerbeth-Kreul, Carolin; Pommereau, Antje; Ruf, Sven; Kane, John L.; Kuntzweiler, Theresa; Hessler, Gerhard; Engel, Christian K.; Shum, Patrick; Wei, LinLi; Czech, Joerg; Licher, Thomas
Classical high-throughput screening (HTS) technologies for the analysis of ionic currents across biological membranes can be performed using fluorescence-based, radioactive, and mass spectrometry (MS)-based uptake assays. These assays provide rapid results for pharmacological HTS, but the underlying, indirect analytical character of these assays can be linked to high false-positive hit rates. Thus, orthogonal and secondary assays using more biological target-based technologies are indispensable for further compound validation and optimization. Direct assay technologies for transporter proteins are electrophysiology-based, but are also complex, time-consuming, and not well applicable for automated profiling purposes. In contrast to conventional patch clamp systems, solid supported membrane (SSM)-based electrophysiology is a sensitive, membrane-based method for transporter analysis, and current technical developments target the demand for automated, accelerated, and sensitive assays for transporter-directed compound screening. In this study, the suitability of the SSM-based technique for pharmacological compound identification and optimization was evaluated performing cell-free SSM-based measurements with the electrogenic amino acid transporter B 0 AT1 (SLC6A19). Electrophysiological characterization of leucine-induced currents demonstrated that the observed signals were specific to B 0 AT1. Moreover, B 0 AT1-dependent responses were successfully inhibited using an established in-house tool compound. Evaluation of current stability and data reproducibility verified the robustness and reliability of the applied assay. Active compounds from primary screens of large compound libraries were validated, and false-positive hits were identified. These results clearly demonstrate the suitability of the SSM-based technique as a direct electrophysiological method for rapid and automated identification of small molecules that can inhibit B 0 AT1 activity.